Robin Watkins At Home With Family - Watkins, Howard::::::::: (1982)
Christine Watkins holding swaddled Robin Watkins, Adam Watkins and Howard Watkins standing in front of living room fireplace Ebony mother-child art work and over mantle mirror on mantle; fireplace tools and heat blower by fireplace